2005
DOI: 10.1562/2004-08-02-ra-254.1
|View full text |Cite
|
Sign up to set email alerts
|

Self-aggregation of Synthetic Protobacteriochlorophyll-d Derivatives¶

Abstract: 3(1)-Racemically pure zinc 3(1)-hydroxy-13(1)-oxo-porphyrins (zinc methyl 17,18-dehydro-bacteriopheophorbides-d) as well as their 3(1)-demethyl form were prepared by modifying chlorophyll-a through oxidation by 2,3-dichloro-5,6-dicyano-benzoquinone. From visible, circular dichroism and infrared spectral analyses, these synthetic pigments self-aggregated in 1%(vol/vol) tetrahydrofuran and cyclohexane to give large oligomers by an intermolecular bonding of 13-C=O...H-O(3(1))...Zn(central) and pi-pi interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…The observed CD signals which are much stronger than the monomeric ones also suggest the formation of well-ordered aggregates (see Figure b). The red-shift of the Q y peak (2380 cm -1 ) is larger than those of the corresponding chlorin or porphyrin analogues as summarized in Table , and also larger than those of the magnesium analogues (right drawing of Chart ) possessing the 3-(1-hydroxyethyl) group at the C3-position (2170 cm -1 ) . The red-shift of the Q y band of Zn- 2 is reported to be only 1150 cm -1 (731 nm in THF to 798 nm in 1% CH 2 Cl 2 −cyclohexane), apparently due to the steric hindrance around the hydroxyl group of the 1-hydroxyethyl group compared to the hydroxymethyl group.…”
Section: Resultsmentioning
confidence: 90%
“…The observed CD signals which are much stronger than the monomeric ones also suggest the formation of well-ordered aggregates (see Figure b). The red-shift of the Q y peak (2380 cm -1 ) is larger than those of the corresponding chlorin or porphyrin analogues as summarized in Table , and also larger than those of the magnesium analogues (right drawing of Chart ) possessing the 3-(1-hydroxyethyl) group at the C3-position (2170 cm -1 ) . The red-shift of the Q y band of Zn- 2 is reported to be only 1150 cm -1 (731 nm in THF to 798 nm in 1% CH 2 Cl 2 −cyclohexane), apparently due to the steric hindrance around the hydroxyl group of the 1-hydroxyethyl group compared to the hydroxymethyl group.…”
Section: Resultsmentioning
confidence: 90%
“…Since most of the synthetic models prepared mimic the molecular structure of natural BChls by possessing the E-ring, their absorption and emission properties are similar to natural BChls. The self-aggregated porphyrin [23,48] and bacteriochlorin molecules [23,42,49] reported previously have their oligomeric Qy maxima at shorter (640-650 nm) and longer wavelength regions (780-880 nm), respectively, compared with the typical chlorin self-aggregates. These variations are accomplished by modifying the π-conjugated systems of the composite molecules.…”
Section: Oligomeric States Of Zinc Chlorins 1-3: Absorption and Emissmentioning
confidence: 87%
“…It has also been shown that if the 3-formyl group is reduced to hydroxymethyl, the pigment will form stable, aggregated suspensions in non-polar solvents which the natural forms will not. It is thought that these self-aggregating suspensions could be valuable in the construction of novel photoactive nano-devices [16]. In LHCs there are other pigments, particularly carotenoids (carotenes and xanthophylls), which may not only act to increase light absorption in the middle wavebands where chlorophyll does not, but also serve other essential functions including a photoprotective action against damage from UV radiation by dissipation of excess excitation energy [17].…”
Section: Light-harvesting Pigment-protein Complexesmentioning
confidence: 99%
“…It has also been shown that if the 3‐formyl group is reduced to hydroxymethyl, the pigment will form stable, aggregated suspensions in non‐polar solvents which the natural forms will not. It is thought that these self‐aggregating suspensions could be valuable in the construction of novel photoactive nano‐devices [16].…”
Section: Light‐harvesting Pigment–protein Complexesmentioning
confidence: 99%